Carboxyl Group (CO2H) Functionalized Coordination Polymer Nanoparticles as Efficient Platforms for Drug Delivery. Issue 47 (5th October 2014) - Novio, Fernando; Lorenzo, Julia; Nador, Fabiana; Wnuk, Karolina; Ruiz‐Molina, Daniel
Abstract Functionalization of nanoparticles can significantly influence their properties and potential applications. Although researchers can now functionalize metal, metal oxide, and organic polymer nanoparticles with a high degree of precision, controlled surface functionalization of nanoscale coordination polymer particles (CPPs) has remained a significant challenge. The lack of methodology is perhaps one of the greatest roadblocks to the advancement of CPPs into high added‐value drug delivery applications. Here, we report having achieved this goal through a stepwise formation and functionalization protocol. We fabricated robust nanoparticles with enhanced thermal and colloidal stabilities by incorporation of carboxyl groups and these surface carboxyl groups could be subsequently functionalized through well‐known peptide coupling reactions. The set of chemistries that we employed as proof‐of‐concept enabled a plethora of new functional improvements for the application of CPPs as drug delivery carriers, including enhanced colloidal stabilities and the incorporation of additional functional groups such as polyethylene glycol (PEG) or fluorescent dyes that enabled tracking of their cellular uptake. Finally, we ascertained the cytotoxicity of the new CPP nanoparticles loaded with camptothecin to human breast adenocarcinoma (MCF‐7). Efflux measurements show that the encapsulation of camptothecin enhances the potency of the drug 6.5‐fold and increases the drug retention within the cell.